A First Course in String Theory (Second Edition) - Zwiebach, B (Cambridge University Press, 2013)
This book has two parts. Part I is called “Basics,” and Part II is called “Developments.” Part I begins with Chapter 1 and concludes with Chapter 14. Part II comprises the rest of the book: it begins with Chapter 15 and it ends with Chapter 26.